The ICD Family of Classifications - Gersenovic, M. (Methods of Information in Medicine, 1995)
The history from the Sixth to the Ninth Revisions of the ICD is described. The 10th revision is presented as the 21st Century classification. The preparation of the ICD-10 included a long process with two expert committee meetings. A classification of diseases can be defined as a system of categories to which morbid entities are assigned according to established criteria. The pupose of the ICD is to permit the systematic analysis, interpretation and comparison of mortality and morbidity data collected in different countries or areas and at different times. In practice, the ICD has become the international standard diagnostic classification for all general epidemiological and many health management purposes. It was felt that the main ICD (the three- and four-character classification), covered by three volumes of ICD-10, could not incorporate all this additional information and remain accessible, and relevant to its traditional users, so the idea arose of a “family” of disease and health-related classifications, including volumes published separately form the main ICD, to be used as required. A statistical classification of diseases must be confined to a limited number of mutually exclusive categories, able to encompass the whole range of morbid condition, and must have well defined place in the list of categories. Consequently, throughout the classification, there will be residual categories for other and miscellaneous conditions that cannot be allocated to the more specific categories. As few conditions as possible should be classified to residual categories. Consequently, throughout the classification, there will be residual categories for other and miscellaneous conditions that cannot be allocated to the more specific categories. As few conditions as possible should be classified to residual categories. A broad description of ICD-10 itself, including information on applications, conventions, and general principles for use are described.
Keywords: ICD; Main ICD; Classification of Diseases